English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5(-7+n)-(3n-7)=-(-3+n)-5n+9

for the solution set i got 6.66
can anyone just make sure

2007-01-28 13:49:14 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

n=-5

factor everything out

-35+5n-3n+7 = 3-n-5n+9
2n -28 = 12 -6n
8 n = 40
n=5

2007-01-28 13:57:29 · answer #1 · answered by Bob 4 · 1 0

You are solving for n. Plug your answer into the equation and solve it. Both sides should be equal. I'm not going to give you the answer. Just collect all the terms and solve. Hint: if you expand the equation you will get -35+5n-3n+7=3-n-5n+9.

2007-01-28 22:04:35 · answer #2 · answered by LJMan 2 · 0 0

5(-7+n)-(3n-7)=-(-3+n)-5n+9
-35+5n -3n+7 = -3 +n -5n +9

-28 +2n = 6 -4n
-34 = -6n

-34/-6 =n
n= 5.6666

2007-01-28 21:55:37 · answer #3 · answered by teachbio 5 · 0 2

-28 + 2n = 12 -6n
n = 5

2007-01-28 21:57:42 · answer #4 · answered by Captain_Knotoworry 1 · 0 0

fedest.com, questions and answers